Git version control cookbook - Olsson, Aske (Packt Publishing, 2014)
In Detail Starting with the Git data model, you will learn how Git stores files and how it looks at commits. You will then learn how you can recover from mistakes; from committing on the wrong branch to recovering lost commits/files. Next, you will discover how you can force rebase on some branches and use regular Git merge on other branches. You will also learn how to extract information from the repository. As you progress through this book, you will learn how you can automate the usual Git processes by utilizing the hook system built into Git. The book also covers advanced repository management, including different options to rewrite the history of a Git repository. Finally, you will discover how you can work offline with Git, how to track what is going on behind the scenes, and how to use the stash for different purposes. Approach This practical guide contains a wide variety of recipes, taking you through all the topics you need to know about to fully utilize the most advanced features of the Git system. Who this book is for If you are a software developer or a build and release engineer who uses Git in your daily work and want to take your Git knowledge to the next level, then this book is for you. To understand and follow the recipes included in this book, basic knowledge of Git command-line code is mandatory.